Experimental and numerical study of the role of crystallographic texture on the formability of an electro-galvanized steel sheet - Signorelli, Javier Walter (2012)
In this work, the influence of plastic anisotropy on forming-limit strains for a drawing-quality steel sheet was investigated. For this purpose, hourglass-type samples, taken at 0◦, 45◦ and 90◦ with respect to the sheet rolling direction were tested with a typical punch and die fixturing. Numerical simulations were carried out in order to validate two viscoplastic (VP) polycrystalline models, self-consistent (SC) and fullconstraint Taylor-type (FC), in conjunction with the Marciniak and Kuczynski (MK) localization approach. The observed shift to the right in the minimum of the forming limit diagram (FLD), inherent to Nakazima test, was taken into account in the simulations. Keeping the set of adjustable parameters to a minimum in the calibration of the viscoplastic polycrystal model, only the material’s initial texture and a power law fit to the tensile data needed to be measured. Without other adjustments to either model, MK-VPSC gives realistic predictions over the entire FLD, while the MK-FC predictions only follow the measured limit curve on the tensile side of plane strain. In the positive biaxial quadrant of the FLD, MK-FC predicts unrealistic high limit values. It was found that, despite these extremely high limit values, the similarity in the measured limit strains for the three sample orientations is captured by both models. However, a consistency in the MK-VPSC predictions indicates that this model seems to be a more suitable tool for describing the role of crystallographic texture on the sheet metal forming processes. sheet rolling direction were tested with a typical punch and die fixturing. Numerical simulations were carried out in order to validate two viscoplastic (VP) polycrystalline models, self-consistent (SC) and fullconstraint Taylor-type (FC), in conjunction with the Marciniak and Kuczynski (MK) localization approach. The observed shift to the right in the minimum of the forming limit diagram (FLD), inherent to Nakazima test, was taken into account in the simulations. Keeping the set of adjustable parameters to a minimum in the calibration of the viscoplastic polycrystal model, only the material’s initial texture and a power law fit to the tensile data needed to be measured. Without other adjustments to either model, MK-VPSC gives realistic predictions over the entire FLD, while the MK-FC predictions only follow the measured limit curve on the tensile side of plane strain. In the positive biaxial quadrant of the FLD, MK-FC predicts unrealistic high limit values. It was found that, despite these extremely high limit values, the similarity in the measured limit strains for the three sample orientations is captured by both models. However, a consistency in the MK-VPSC predictions indicates that this model seems to be a more suitable tool for describing the role of crystallographic texture on the sheet metal forming processes. sheet rolling direction were tested with a typical punch and die fixturing. Numerical simulations were carried out in order to validate two viscoplastic (VP) polycrystalline models, self-consistent (SC) and fullconstraint Taylor-type (FC), in conjunction with the Marciniak and Kuczynski (MK) localization approach. The observed shift to the right in the minimum of the forming limit diagram (FLD), inherent to Nakazima test, was taken into account in the simulations. Keeping the set of adjustable parameters to a minimum in the calibration of the viscoplastic polycrystal model, only the material’s initial texture and a power law fit to the tensile data needed to be measured. Without other adjustments to either model, MK-VPSC gives realistic predictions over the entire FLD, while the MK-FC predictions only follow the measured limit curve on the tensile side of plane strain. In the positive biaxial quadrant of the FLD, MK-FC predicts unrealistic high limit values. It was found that, despite these extremely high limit values, the similarity in the measured limit strains for the three sample orientations is captured by both models. However, a consistency in the MK-VPSC predictions indicates that this model seems to be a more suitable tool for describing the role of crystallographic texture on the sheet metal forming processes. ◦, 45◦ and 90◦ with respect to the sheet rolling direction were tested with a typical punch and die fixturing. Numerical simulations were carried out in order to validate two viscoplastic (VP) polycrystalline models, self-consistent (SC) and fullconstraint Taylor-type (FC), in conjunction with the Marciniak and Kuczynski (MK) localization approach. The observed shift to the right in the minimum of the forming limit diagram (FLD), inherent to Nakazima test, was taken into account in the simulations. Keeping the set of adjustable parameters to a minimum in the calibration of the viscoplastic polycrystal model, only the material’s initial texture and a power law fit to the tensile data needed to be measured. Without other adjustments to either model, MK-VPSC gives realistic predictions over the entire FLD, while the MK-FC predictions only follow the measured limit curve on the tensile side of plane strain. In the positive biaxial quadrant of the FLD, MK-FC predicts unrealistic high limit values. It was found that, despite these extremely high limit values, the similarity in the measured limit strains for the three sample orientations is captured by both models. However, a consistency in the MK-VPSC predictions indicates that this model seems to be a more suitable tool for describing the role of crystallographic texture on the sheet metal forming processes.